Legislative provisions for waṣiyyah wājibah in Malaysia and~Indonesia: To what extent do~they differ in practice? - Suhaili Alma'amun; Mohd Khairy Kamarudin; Wan Nadiah Wan Mohd Nasir; Nasrul Hisyam Nor Muhamad; Riayati Ahmad (ISRA International Journal of Islamic Finance, 2022)
Purpose - This research aims to examine and compare differences in waṣiyyah wājibah (obligatory bequest) (WW) practices in Malaysia and Indonesia. Design/methodology/approach - This is an exploratory qualitative research, employing a thematic analysis approach. Six Muslim Wills (State) Enactments [Enakmen Wasiat Orang Islam (Negeri)] in Malaysia, Islamic Law Compilation (Kompilasi Hukum Islam) in Indonesia, two fatwas (ruling in religious matters) and one court case from each country are analysed. Data is collected from official government websites and other reliable search engines. Findings - First, the findings show that the WW practice in both countries is similar regarding the quantum of the beneficiaries' entitlement. However, the practice varies between both countries in terms of the types of beneficiaries and how the bequest is distributed. Second, this study shows the potential of WW as an estate planning instrument to complement the existing instruments in each country, especially when addressing family members who are not entitled to succeed by farāʾiḍ (Islamic inheritance law). Practical implications - The provision of relevant laws and regulations regarding WW needs to be formulated to guarantee the well-being of dependants. The differences in practice between the two countries can be a guideline to expand the WW scope and context to other Muslim countries. Originality/value - This study is the first attempt to compare WW between two Muslim-majority countries focusing on relevant laws, court cases and regulations.
Keywords: 330; Islamic inheritance; Islamic law compilation; Muslim wills (state) enactments; Waṣiyyah wājibah (WW)